2021
DOI: 10.3390/ijms22147486
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Very High Dose Local Vessel Wall Statin Administration: Poly(L,L-Lactide) Biodegradable Microspheres with Simvastatin for Drug Delivery System (DDS)

Abstract: Atherosclerosis involves an ongoing inflammatory response of the vascular endothelium and vessel wall of the aorta and vein. The pleiotropic effects of statins have been well described in many in vitro and in vivo studies, but these effects are difficult to achieve in clinical practice due to the low bioavailability of statins and their first-pass metabolism in the liver. The aim of this study was to test a vessel wall local drug delivery system (DDS) using PLA microstructures loaded with simvastatin. Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another approach by Wacinski et al described the use of novel biodegradable poly(L,L‐LA) microparticles loaded with simvastatin (SVPLA) to test as a vessel wall local drug delivery system in the rat model 89 . The chemically injured rat vessels were treated by administrating different concentrations of poly(L,L‐LA) microspheres loaded high local HMG‐CoA inhibitor simvastatin (0.58 mg/kg).…”
Section: Poly(lactic Acid) and Poly(lactic‐co‐glycolic Acid) Based Na...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach by Wacinski et al described the use of novel biodegradable poly(L,L‐LA) microparticles loaded with simvastatin (SVPLA) to test as a vessel wall local drug delivery system in the rat model 89 . The chemically injured rat vessels were treated by administrating different concentrations of poly(L,L‐LA) microspheres loaded high local HMG‐CoA inhibitor simvastatin (0.58 mg/kg).…”
Section: Poly(lactic Acid) and Poly(lactic‐co‐glycolic Acid) Based Na...mentioning
confidence: 99%
“…Another approach by Wacinski et al described the use of novel biodegradable poly(L,L-LA) microparticles loaded with simvastatin (SVPLA) to test as a vessel wall local drug delivery system in the rat model. 89 The chemically injured rat vessels were treated by administrating different concentrations of poly(L,L-LA) microspheres loaded high local HMG-CoA inhibitor simvastatin (0.58 mg/kg). The results concluded that the use of SVPLA microspheres with an average diameter and percentage of drug loading 6.4 μm and 8.1% respectively, is enough to limit the inflammatory reactions in the endothelium and vessel wall.…”
Section: Poly(lactic Acid) and Poly(lactic-co-glycolic Acid) Based Na...mentioning
confidence: 99%